Tingkat Kemiskinan Di Pulau Papua Tahun 20011-2017 (Jurnal Ekonomi dan Kebijakan Pembangunan, 2018)
Poverty alleviation is one of the goals of economic development. During 2011 to 2017, both Papua and West Papua Provinces where located in Papua Island had the first and second highest poverty rate in Indonesia. This study analyzed the factors that influenced poverty rate in Papua Island during 2011 to 2017 used the panel regression model. The results of the study showed GRDP per capita of the Mining and Quarrying sector, GRDP per capita of the Construction sector, and education had a significant effect on reducing poverty.